Association of Lipid Profile with Preeclampsia - Akter, Ruma; Haque, Nadira; Hosain, Nazmul; Akter, Nargis; Islam, Fahmida; Hasan, Tmanna; Sumona, Rezwana Haque (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Preeclampsia is a pregnancy specific disorder characterized by hypertension and proteinuria after 20 weeks of gestation. Abnormal lipid profile is known to be associated with development of symptoms of preeclampsia. Obective of the study includes evaluating the association oflipid profile with preeclampsia. Materials and methods: This case control study was carried out in the Department of Obstetrics & Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, between 1st October 2017 and 30th September 2018. 46 pregnant women clinically diagnosed as preeclampsia were selected as cases (Group I) and equal number of age, parity and gestational age group matched apparently healthy normotensive pregnant women were selected as control (Group II) for the study. Fasting blood sample were collected and estimated for serum lipid profile. Demographic data and lipid profile were analyzed by using student t-test and chi square test, a p-value of <0.05 was considered significant. Odds ratio with 95% Confidence Interval was calculated to assess the risk. Pearson's correlation coefficient test and Spearman's rank correlation coefficient test were done to assess the correlation. Results: Mean total cholesterol in preeclampsia group was 245.2±59.9 mg/dl and normal pregnancy group was 192.5±32.5 mg/dl. Mean HDL-C in preeclampsia group was 50.9±11.3 mg/dl and in normal pregnancy group was 50.3±11.1m g/dl. Mean LDL-C in preeclampsia group was 141.1±54.1 mg/dl and normal pregnancy was 100.9±31.8 mg/dl. Mean triglycerides in preeclampsia group was 272.5±84.8 mg/dl and in normal pregnancy group was 178.9±48.2 mg/dl. Total cholesterol, LDL-C and triglycerides, all were increased in preeclampsia as compared to normal pregnancy. These were statistically significant (p<0.05) but no significant difference was noted in HDL-C level between the two groups (p>0.05). Significant positive correlation between blood pressure and levels of total cholesterol, LDL-C and triglycerideswas revealed by Pearson's correlation test. Spearman's rank correlation coefficient test also revealed positive correlation of total cholesterol and triglycerides with the severity of preeclampsia. Conclusion: Dyslipidemia is significantly evident in preeclampsia and may play an important pathological role. Estimating serum lipid profile is a simple screening test, helps to recognize dyslipidemia in early second trimester of pregnancy who are at risk of preeclampsia. JCMCTA 2022 ; 33 (2) : 100-105